ANALISIS PEMANFAATAN SKB PER-32/PJ/2013 OLEH WAJIB PAJAK (Studi pada Koperasi dan UMKM di Kota Kediri) - Indah Karismawati; Akie Rusaktiva Rustam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objective of this research is to understand the usage of SKB PER-32/PJ/2013 by Wajib Pajak Badan PP 46 and other facility to return PPh 22 and PPh 23 has been levied as efforts to tax saving. The study used descriptive qualitative method. The infromants that used are 1 Koperasi and 4 Usaha Mikro Kecil dan Menengah (Medium and Micro Entreprise) in Kediri. The key informants are 1 Koperasi Pegawai and 4 Usaha Mikro Kecil dan Menengah (Medium and Micro Entreprise). The research finding revealed that (1) From 5 informants only 1 Wajib Pajak used SKB PER-32/PJ/2013 (2) There are Wajib Pajak prefer let the PPh 22 and 23 which has been levied to be investigated by goverment (3)There are some Wajib Pajak can get tax saving more than 50% if used SKB PER-32/PJ/2013 (4)The levies can reject SKB PER-32/PJ/2013 because of corporate policy.Keywords : usage, SKB PER-32/PJ/2013, Wajib Pajak Badan PP 46